Mutational Inactivation of Herpes Simplex Virus 1 MicroRNAs Identifies Viral mRNA Targets and Reveals Phenotypic Effects in Culture - Flores, Omar (American Society for Microbiology, 2013)
Herpes simplex virus 1 (HSV-1), a ubiquitous human pathogen, expresses several viral microRNAs (miRNAs). These, along with the latency-associated transcript, represent the only viral RNAs detectable in latently infected neuronal cells. Here, for the first time, we analyze which HSV-1 miRNAs are loaded into the RNA-induced silencing complex (RISC), the key effector of miRNA function. Only 9 of the 17 reported HSV-1 miRNAs, i.e., miR-H1 to miR-H8 plus miR-H11, were found to actually load into the RISC. Surprisingly, this analysis also revealed that HSV-1 miRNAs loaded into the RISC with efficiencies that differed widely; <1% of the miR-H1-3p miRNA detectable in HSV-1-infected cells was loaded into the RISC. Analysis of HSV-1 mutants individually lacking the viral miR-H2, miR-H3, or miR-H4 miRNA revealed that loss of these miRNAs affected the rate of replication of HSV-1 in neuronal cells but not in fibroblasts. Analysis of mRNA and protein expression, as well as assays mapping viral miRNA binding sites in infected cells, showed that endogenous HSV-1 miR-H2 binds to viral ICP0 mRNA and inhibits its expression, while endogenous miR-H4 inhibits the expression of the viral ICP34.5 gene. In contrast, no viral mRNA target for miR-H3 could be detected, even though miR-H3, like miR-H4, is perfectly complementary to ICP34.5 mRNA. Together, these data demonstrate that endogenous HSV-1 miRNA expression can significantly alter viral replication in culture, and they also identify two viral mRNA targets for miR-H2 and miR-H4 that can partially explain this phenotype.